“La interculturalidad y su incidencia en la comunicación interna del Gobierno Autónomo Descentralizado de la Parroquia Flores período julio 2015 a diciembre 2015” - Verdezoto López, Jessica Daniela (2016)
This research project aims to establish the intercultural influence in the internal communication of the decentralized autonomous government in Flores parish. The first chapter, culture, defines the culture from the perspective of different authors. It explores cultural identity taking into account various aspects that define a culture. Then, it describes the indigenous cultural identity. The second chapter, entitled interculturality, describes the intercultural background, it discusses the concept of interculturality, multiculturality, and their differences. Then in another paragraph the concept of hybrid cultures, make appointment to make an approach with the issue of this research. The third chapter, called communication, reference is made to its concept, outlining the intercultural communication and its main aspects. They are the purposes and functions of public relations. It defines the internal communication, functions, forms and the same strategies. Similarly focuses on the conceptualization of communication in companies, institutions and organizational communication. The fourth chapter, the cultural anthropological culture, establishes its meaning and its communicative relationship. The fifth chapter, Flores parish, summarizes its history, the number of inhabitants and it indicates the name of the members of the autonomous decentralized government who run Flores parish.